Model Pengelolaan Dana Otonomi Khusus terhadap Kesejahteraan Masyarakat di Aceh Ditinjau dari Maqashid Syariah - Ikbal Ramzani (Ar-Raniry: International Journal of Islamic Studies, 2020)
The purpose of this study is to find out how the construction of Sharia Maqashid model in budgeting policy of special autonomy fund given by the Central Government to Aceh Province based on Law No. 11, 2006 concerning Aceh Government. The research method used was a descriptive qualitative method, which collects, arranges, manages, and analyzes data to describe a particular situation. So that, it can conclude that the application of the particular autonomy fund budget was focused on several dimensions, namely infrastructure, empowerment of the people's economy, poverty alleviation, education, health, social and special features of Aceh. The results of this study indicated that the use of special autonomy funds channelled by the central government to the Aceh government has continuously increased. However, in the application, its use has not entirely dominated dharuriyyah dimension consists of protection of religion (hifẓ al-din), protection of life (hifẓ al -nafs), protection of thoughts (hifẓ al-'aql), protection of heredity (hifẓ al-nasl), protection of property (hifẓ al-mal), and protection of the environment (hifẓ al-biah). Therefore, the special autonomy fund can be projected to improve community welfare by using three dimensions of hierarchy, including dharuriyyah, hajjiyyah and tahsiniyyah as the basis of Aceh's future development. The achievement of Aceh's development must be based on Islamic law. Because the application of the special autonomy fund is part of  Maqashid Sharia as mentioned in theological, philosophical and sociological foundations of Law No. 11, 2006 concerning of Aceh Government, so, the society can achieve the happiness of the hereafter world and the welfare of the people with justice whether from economic factors or law security of citizens' political rights.